Effect of Nitrate, Ammonium and Urea on Growth and Pinnatoxin G Production of Vulcanodinium rugosum - Eric Abadie; Lamia Kaci; Tom Berteaux; Philipp Hess; Véronique Sechet; Estelle Masseret; Jean Luc Rolland; Mohamed Laabir (Marine Drugs, 2015)
Vulcanodinium rugosum, a recently described dinoflagellate species producing a potent neurotoxin (pinnatoxin G), has been identified in French Mediterranean lagoons and was responsible for recurrent episodes of shellfish toxicity detected by mouse bioassay. Until now, the biology and physiology of V. rugosum have not been fully investigated. We studied the growth characteristics and toxicity of a V. rugosum strain (IFR-VRU-01), isolated in the Ingril lagoon in June 2009 (North-Western French Mediterranean Sea). It was cultivated in Enriched Natural Sea Water (ENSW) with organic (urea) and inorganic (ammonium and nitrate) nitrogen, at a temperature of 25 °C and irradiance of 100 μmol/m2·s−1. Results showed that ammonium was assimilated by cells more rapidly than nitrate and urea. V. rugosum is thus an osmotrophic species using urea. Consequently, this nitrogen form could contribute to the growth of this dinoflagellate species in the natural environment. There was no significant difference (Anova, p = 0.856) between the growth rate of V. rugosum cultivated with ammonium (0.28 ± 0.11 day−1), urea (0.26 ± 0.08 day−1) and nitrate (0.24 ± 0.01 day−1). However, the production of chlorophyll a and pinnatoxin G was significantly lower with urea as a nitrogen source (Anova, p < 0.027), suggesting that nutritional conditions prevailing at the moment of the bloom could determine the cellular toxicity of V. rugosum and therefore the toxicity measured in contaminated mollusks. The relatively low growth rate (≤0.28 day−1) and the capacity of this species to continuously produce temporary cysts could explain why cell densities of this species in the water column are typically low (≤20,000 cells/L).